Effect of Storange Time on the Quality of Shrimp Paste - Isdaryanti Isdaryanti; Musrifah Tahar; Ayu Indayanti Ismail (Fakultas Pertanian Universitas Muara Bungo, 2022)
Shrimp paste is a product of fermentation that every time it will continue to be degradated by microorganisms. The degradation has a time limit to continue to produce the best quality shrimp paste based on the value of the Indonesian National Standard. The purpose of this study was to determine the quality of shrimp paste up to a storage period of 3 months 7 days. This study was used a randomized block design (RBD) method with different storage times of 7, 37 and 67 days. The quality parameters of shrimp paste used were physicochemical value by measuring pH and salt content and proximate analysis by measuring protein, fat, carbohydrate, ash content and air content. The results were showed that the pH of the shrimp paste was in the alkaline range from 7.72 to 7.33, the proportion of salt content was 5.09%. Proximate analysis were showed protein content (37.05%), fat (3.26%), carbohydrates (4.23%), ash content (19.45%), and air content (36%). Based on the results of this study, it was found that shrimp paste with a storage period of 3 months and 7 days met national standards except for the ash content.